Políticas de ampliação da jornada escolar: a implantação do Programa Mais Educação em Igarapé-Miri/PA - SOUSA, Luísete do Espírito Santo (Universidade Federal do Pará, 2017)
This dissertation analyzes the expansion policy of the school day in the Brazilian public school, through the implementation of the Programa Mais Educação in the Municipal Department of Education and two (02) schools of Igarapé-Miri, in Pará State, in the period of 2011 to 2014. It is in line with the discussions on integral education and full time education which, in recent years, have been constant subject of studies in academia. The methodological option for qualitative research enabled us to promote an analysis of educational reality built through dialogue with our object in an intense relationship with the subjects and documents produced in that context. The Case Study, as a methodological process, allowed us to observe the peculiarity and uniqueness of PME in Igarapé-Miri, allowing the categorization of nuances that the implementation of this Program has taken, and the conceptions shared in the Municipal Department of Education and schools. This approach was also conducted with bibliographical and documentary research, about the process built-up in this reality. The relevance of this study is mainly on the possibility to observe how the Brazilian educational policies which proposes to extend the time of education in the perspective of Integral Education/full-time education can be presented. From the analysis, it was found that the implementation of PME has enabled significant contributions in overcoming the reduced public school shift that has been focused in content and disciplines. Contradictorily, in this locus, it has not yet been possible to verify that the use of the Program has been a successful strategy for the promotion of Integral Education/full-time education because the observed experiences reveal that the lack of adequate infrastructure, the need for training and professionals development and the lack of curriculum guidelines has hampered this change in school.